Sound, image, and national imaginary in the construction of Latin/o American identities - Fernández L'Hoeste, Héctor D. 1962-; Vila, Pablo 1952- (Lexington Books, 2018)
This book explores the key role of sound and image in the perception of nations throughout the history of the Americas. It subverts the strict chronology previously upheld by historians regarding the formation of national identities by looking at the development of countries in varied cultural, economic, and political situations
Keywords: Popmusik; Kulturelle Identität; Lateinamerika; Group identity / Latin America; National characteristics, Latin American; Music / Latin America / History and criticism; Group identity; Music; Latin America; Criticism, interpretation, etc; Aufsatzsammlung